A miniature laser diode interferometer with self-compensation of retroreflector's motion errors for displacement feedback of small-sized micro/nano motion stages. (December 2021) - Cai, Yindi; Xie, Bo; Wen, Zhixiang; Fan, Kuang-Chao
Highlights: The effects of the reflector's motion errors on an interferometer are analyzed. Variations of the optical path difference caused by motion errors are investigated. A compensation model for the interferometer is established. The interferometer is improved by integrating two error detectors into it. The accuracy of the interferometer is improved 50% after error compensation. Abstract: The effects of the retroreflector's motion errors on the measurement accuracy of a miniature laser diode interferometer (MLDI), which is designed as a displacement feedback device for small-sized micro/nano motion stages, are investigated. A novel method of investigating the variation of the optical path difference of the interferometer is proposed. It is verified that all motion errors of the retroreflector will affect the measurement accuracy. The MLDI system is, thus, improved by integrating a straightness error detector and an angular error detector into it to compensate the measurement error induced by the retroreflector's motion errors according to the proposed compensation model. The improved MLDI system can not only measure and compensate the retroreflector's motion errors, but also achieve multi-degree-of-freedom (DOF) measurement. A series of experiments are carried out to verify the effectiveness of the proposed compensation model and the capable of the improved MLDI system.